Optimised paediatric CT dose at a tertiary children's hospital in Japan: a 4-y single-centre analysis. Issue 1 (10th February 2015) - Nakada, Y.; Fujiwara, M.; Yakami, M.; Yokoyama, T.; Shirayama, A.; Yamamoto, H.; Nabatame, K.; Obara, S.; Akahane, K.; Blyth, B. J.; Miyazaki, O.; Date, H.; et al.
Abstract : Since diagnostic reference levels (DRLs) for children are not currently established in Japan, the authors determined local DRLs for the full range of paediatric CT examinations in a single tertiary care children's hospital. A retrospective review of 4801 CT performance records for paediatric patients (<15 y old) who had undergone CT examinations from 2008 to 2011 was conducted. The most frequent examinations were of the head (52 %), followed by cardiac (15 %), temporal bone (9 %), abdomen (7 %), chest (6 %) and others (11 %). Approximately one-third of children received two or more CT scans. The authors' investigation showed that mean CTDIvol and DLP for head, chest and abdomen increased as a function of age. Benchmarking of the results showed that CTDIvol, DLP and effective dose for chest and abdomen examinations in this hospital were below average, whereas those for the head tended to be at or slightly above average of established DRL values from five countries. The results suggest that CT examinations as performed in a tertiary children's hospital in Japan are well optimised.